2014
DOI: 10.1111/bjep.12036
|View full text |Cite
|
Sign up to set email alerts
|

The role of speech prosody and text reading prosody in children's reading comprehension

Abstract: The variance that speech prosody explained in reading comprehension scores should not be neglected. Speech prosody seems to facilitate the construction of meaning in written language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 66 publications
5
49
1
2
Order By: Relevance
“…For instance, Miller and Schwanenflugel (2006) found that children who used more pitch changes while reading aloud understood the text better. Veenendaal, Groen, and Verhoeven (2014) found that, besides reading aloud prosody, proficiency in speech prosody (as elicited in a story-telling task) had a positive effect on reading comprehension. Whalley and Hansen (2006) demonstrated that children with a poorer performance on accent placement in a reiterative speech task performed poorer on reading comprehension than children with a better prosodic proficiency (see also Holliman, Wood, & Sheehy, 2010a, 2010b.…”
Section: Focus Structure In Language Processingmentioning
confidence: 96%
“…For instance, Miller and Schwanenflugel (2006) found that children who used more pitch changes while reading aloud understood the text better. Veenendaal, Groen, and Verhoeven (2014) found that, besides reading aloud prosody, proficiency in speech prosody (as elicited in a story-telling task) had a positive effect on reading comprehension. Whalley and Hansen (2006) demonstrated that children with a poorer performance on accent placement in a reiterative speech task performed poorer on reading comprehension than children with a better prosodic proficiency (see also Holliman, Wood, & Sheehy, 2010a, 2010b.…”
Section: Focus Structure In Language Processingmentioning
confidence: 96%
“…Recent studies have consistently shown that text reading prosody—a constituent of text reading fluency— and reading comprehension are associated (Benjamin & Schwanenflugel, 2010; Kuhn & Stahl, 2003; Miller & Schwanenflugel, 2006, 2008; Rasinski, Rikli, & Johnston, 2009; Veenendaal, Groen, & Verhoeven, 2014, 2015). Text reading prosody refers to the extent to which children use appropriate intonation, such as phrasing, use of pauses, and signalling of word boundaries which makes reading aloud sound more like natural speech.…”
mentioning
confidence: 99%
“…This study sought to describe the performance of fluent adults in different speech rate measures. Studies show that the analysis of speech rate has proven valuable in evaluating individuals with typical and altered speech development (1,2,15,16,(19)(20)(21)(22)(23) . However, there is no consensus on the best methodology for assessing speech rate, which should be associated with the clinician's objective.…”
Section: Discussionmentioning
confidence: 99%
“…These temporal measures and variables were used in further studies of the reading performance of adults (14) , of the reading performance of children (15) , of the reading performance of children with dyslexia (16) , in the speech performance of military commanders (17) , in the speech performance of stutterers and fluent individuals (5,18) , among others.…”
Section: Introductionmentioning
confidence: 99%